Drainage Network Alignment for Namakkal District By Using GIS - Subramani, T; Vinothkumar, S (International Journal of Engineering and Technology, 2018)
Drainage specifies the groundwater conditions and assurance of speed and groundwater stream of a region. Arrangement of drainage as characteristic and technogenic segments on level of drainage basis. Alignment of sewers and water drains must has regular drainage pattern for maintain a strategic distance of surface obstacles. Arrangement of drains is a typical methodology consider elements like geography, land use, land cover and right of way will assume vital part. For the preparation of topographic data used advanced GIS techniques. The following results will obtained using GIS for Namakkal dist such as erosion network, density and depth of erosion network, as well as land surface sloping and further total evaluation as a drainage parameters. Also mentioned the valuable suggestions for better drainage management and drainage rate and disaster management at the time floods. Â Â